Treatment with morning blue light increases left amygdala volume and sleep duration among individuals with posttraumatic stress disorder - Killgore, William D. S.; Vanuk, John R.; Dailey, Natalie S. (Frontiers in Behavioral Neuroscience, 2022)
Background Posttraumatic stress disorder (PTSD) is associated with numerous cognitive, affective, and psychophysiological outcomes, including problems with sleep and circadian rhythms. We tested the effectiveness of a daily morning blue-light exposure treatment (BLT) versus a matched amber light treatment (ALT) to regulate sleep in individuals diagnosed with PTSD. Moreover, PTSD is also associated with reliable findings on structural neuroimaging scans, including reduced amygdala volumes and other differences in cortical gray matter volume (GMV) that may be indicative of underlying neurobehavioral dysfunctions. We examined the effect of BLT versus ALT on GMV and its association with sleep outcomes. Methods Seventy-six individuals (25 male; 51 female) meeting DSM-V criteria for PTSD (Age = 31.45 years, SD = 8.83) completed sleep assessments and structural neuroimaging scans, followed by random assignment one of two light groups, including BLT (469 nm; n = 39) or placebo ALT (578 nm; n = 37) light therapy daily for 30-min over 6-weeks. Participants wore a wrist actigraph for the duration of the study. After treatment, participants returned to complete sleep assessments and a structural neuroimaging scan. Neuroimaging data were analyzed using the Computational Anatomy Toolbox (CAT12) and Voxel-Based Morphometry (VBM) modules within the Statistical Parametric Mapping (SPM12) software. Results The BLT condition produced significant increases in total time in bed and total sleep time from actigraphy compared to the ALT condition, while ALT improved wake after sleep onset and sleep efficiency compared to BLT. Additionally, BLT led to an increase in left amygdala volume compared to ALT but did not affect hypothesized medial prefrontal regions. Finally, within group correlations showed that improvements in sleep quality and nightmare severity were correlated with increases in left amygdala volume over the course of treatment for the BLT group but not the ALT group. Conclusion In individuals with PTSD, daily exposure to morning blue light treatment was associated with improvements in objective sleep duration and increased volume of the left amygdala compared to amber placebo light treatment, and changes in amygdala volume correlated with subjective improvement in sleep. These findings suggest that daily morning BLT may provide an important non-pharmacologic adjunctive approach for facilitating sleep and neurobehavioral recovery from PTSD.